Mite fauna associated with Cecropia pachystachya TREC. (Urticaceae)-the importance of the plant as reservoir and dissemination means for predatory mites - Lofego, Antonio Carlos [UNESP]; Rezende, José Marcos [UNESP]; Demite, Peterson Rodrigo; Feres, Reinaldo José Fazzio [UNESP] (Systematic and Applied Acarology Society, 2017)
Cecropia pachystachya TREC. (Urticaceae) is a common pioneer plant from South America, which is found on both degraded and preserved environments. Pioneer plants are able to disperse into agricultural environments and to introduce species of mites different from those present amongst the cultivated plants. This study evaluated the mite fauna present on plants of C. pachystachya associated with 18 forest fragment sites in the Northwest region of the state of São Paulo, a region where only 3% of the native vegetation is preserved. High species richness (82 species) and abundance (3,631 specimens) of mites were recorded on the plants, with high variation in species composition among the sites sampled. Regardless the species composition, most of the sites showed predominance of species considered predators, indicating that C. pachystachya provides some type of food for these mites. The data obtained in the study suggest that this plant can be an important reservoir of predatory mites and could facilitate their dissemination from preserved environments to degraded areas or crops.
Keywords: conservation; environmental services; phytophagous mites; predatory mites